The Rhetoric of Speech Presentation in the Israeli Press - Nir, Raphael; Roeh, Itzhak (1993)
Techniques of speech presentation in narrative fiction have been widely described by scholars of both literature and linguistics. In the press, like in fiction, strategies of presentation may be ordered along a continuum reflecting different degrees of directness in reporting the utterances. In the press, speech presentation is a result of a tension between the need to report the statements in standard "journalese" and the wish to communicate a sense of the original utterance. In newspaper headlines, especially in the popular press, direct quotes are rather common. In this way sppech presentation reflects a "rhetoric of trust" and should be viewed as part of creating a "showing" effect and dramatization. In our study we found a relatively high degree of mimesis in popular newspapers, as opposed to quality papers. Another difference lies in the degree of poetical presentation, which is widespread in popular press headlines.